2019
DOI: 10.1002/mc.22970
|View full text |Cite
|
Sign up to set email alerts
|

NFκB2 p52 stabilizes rhogdiβ mRNA by inhibiting AUF1 protein degradation via a miR‐145/Sp1/USP8‐dependent axis

Abstract: Although overexpression of the non‐canonical NFκB subunit p52 has been observed in several tumors, the function and mechanism of p52 in bladder cancer (BC) are less well understood. Here, we aimed at understanding the role and mechanism underlying p52 regulation of BC invasion. Human p52 was stably knockdown with shRNA targeting p52 in two bladder cancer cell lines (T24 and UMUC3). Two constitutively expressing constructs, p52 and p100, were stably transfected in to T24 or UMUC3, respectively. The stable trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…18 In addition, USP8 is capable of being modulated by transcription factors. 19 JASPAR database prediction showed that YY1 could bind to the USP8 promoter. After silencing YY1, the enrichment of YY1 in the USP8 promoter was decreased, along with the mRNA expression of USP8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In addition, USP8 is capable of being modulated by transcription factors. 19 JASPAR database prediction showed that YY1 could bind to the USP8 promoter. After silencing YY1, the enrichment of YY1 in the USP8 promoter was decreased, along with the mRNA expression of USP8.…”
Section: Discussionmentioning
confidence: 99%
“…18 USP8 can be modulated by transcription factors. 19 Furthermore, the JASPAR database shows that YY1 can bind to the USP8 promoter. Nevertheless, the exact interaction between USP8 and YY1 and whether this interaction affects cognitive impairment after SAE remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated that specific protein 1 (Sp1) decreased USP8 transcription. Huang et al revealed that inhibited sp1 expression by activating miR-145 [49]. In our future study, we need to address the molecular mechanism which H2S modulates USP8.…”
Section: Limitationmentioning
confidence: 91%
“…They have identified three different pathways—RhoGDI2/miR-200c/JNK2/Sp1/MMP2 pathway, XIAP/Erk/nucleolin/RhoGDI2 and, lastly, miR-145/Sp1/USP8/AUF1/RhoGDI2 pathway—through which they show that RhoGDI2 promotes BLCA invasion in vitro and lung metastasis in vivo. They observe that RhoGDI2 acts as a tumour and metastasis promoter, despite being widely demonstrated in the past as a metastasis suppressor, with no effect on the tumour [ 91 , 92 , 93 ]. Further investigations are required to better define the exact function of RhoGDI2 in BLCA.…”
Section: Regulatory Functions Of Rhogdi2 In Cancermentioning
confidence: 99%